IMPLEMENTASI DATA MINING UNTUK MENGANALISA POLA PENJUALAN MENGGUNAKAN METODE K-MEANS PADA CV. HAVAS P2S2 - Alfan Jamil; Zaehol Fatah (CV. Denasya Smart Publisher, 2024)
Sales are an important aspect in the continuity of company operations, including CV. Hafas P2S2 which is engaged in the distribution of bottled drinking water products. In order to increase the effectiveness of marketing strategies and stock management, it is important to analyze sales patterns that occur. This research aims to implement data mining techniques using the K-means method to analyze sales patterns at CV. Memorize P2S2. The K-means method was chosen because of its ability to find associative relationships between items that are often purchased together in transactions. The data used in this research involves sales information recorded in the company system. The results of applying the K-means algorithm show that there are certain combinations of items that are often sold together, which provides valuable insights for companies in terms of stock management and marketing strategies. It is hoped that these findings can help CV. Hafas P2S2 in improving operational efficiency and maximizing profit potential by better understanding customer demand patterns. Thus, the implementation of data mining through the K-means method makes a significant contribution to data-based decision making in the company's sales sector.